The Relationships between Belief, Attitude, Subjective Norm, and Behavior Towards Infant Food Formula Selection: The Views of the Malaysian Mothers - T. Ramayah; Aizzat Mohd. Nasurdin; Mohd. Nasser Noor; Quah Boon Sin (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2004)
The purpose of the study is to determine the relationships between belief, attitude, subjective norm, intention, and behavior towards the choice of infant food based on the Theory of Reasoned Action (TRA). An analysis on a sample of 108 mothers indicates that the TRA could be used in predicting choice decision of infant food formulas by explaining 57 percent of the variance in the behavioral intention. The subjective norm component had a higher predictive power than the attitudinal component. Of this normative component, parents or relatives and doctors were found to be more influential. Intention to choose an infant formula was also influenced by family income. The belief outcomes in evaluating a premium infant formula and economic infant formula were found to be different. For premium infant formula, brand trusted, closest to breast milk and nutrients content were identified as the dominant attributes. In contrast, availability, affordable, and nutrients content were identified as the prime beliefs in evaluating economic infant formula. Implications of the findings are discussed.